If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 3 = -3x + 3 + 11x Reorder the terms: 3 + 8x = -3x + 3 + 11x Reorder the terms: 3 + 8x = 3 + -3x + 11x Combine like terms: -3x + 11x = 8x 3 + 8x = 3 + 8x Add '-3' to each side of the equation. 3 + -3 + 8x = 3 + -3 + 8x Combine like terms: 3 + -3 = 0 0 + 8x = 3 + -3 + 8x 8x = 3 + -3 + 8x Combine like terms: 3 + -3 = 0 8x = 0 + 8x 8x = 8x Add '-8x' to each side of the equation. 8x + -8x = 8x + -8x Combine like terms: 8x + -8x = 0 0 = 8x + -8x Combine like terms: 8x + -8x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 6m+m-3rpm= | | 6m+m-3rp+2rpm= | | 0=[x-(1+2i)][x-(1-2i)](x-1)(x+2) | | 0=[x-(2+3i)][x-(2-3i)](x+1)(x-2) | | -3x-11=5x+21 | | 0=[x-(2+2i)][x-(2-2i)](x+1)(x-2) | | ydx+(x+y)st=0 | | y=3x^4-4x^3-12x^2+2 | | 3.2=-6u+22.4 | | 42=4a+9 | | 7(x-8)+17=4(x-6) | | 0.7(X+20)+0.9x=78 | | 8.75=u | | -2x+2=-2(2x+5) | | 2(5x+1)=6x-(2-4x) | | 0.4(x-6)=4.0 | | y=5x^2-6x | | 6-8x-2=-48+3x-14 | | 3x=4+3x-1 | | 10x-(2x+4)=60 | | -(12-2x)=-7 | | .2x+c=6 | | x^2-12x+81=0 | | 0.5(4-3)2=x | | 0.5(4-1)2=x | | 0.5(5-3)2=x | | 0.5(5-3)=x | | 0.5(5-2)2= | | y+2.9=5.65 | | 0.5(5-3)2= | | 0.5(5-3)= | | Ln(7)-ln(x)=-0.06 |